PENGARUH KUALITAS PELAYANAN SAMSAT DRIVE THRU BATUBULAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN GIANYAR - Komang Maitha Gauri Cahyani; Ni Putu Anik Prabawati; I Putu Dharmanu Yudartha (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to determine the influence of the quality of Samsat Drive Thru Batubulan service on the compliance of motor vehicle taxpayers in Gianyar Regency. This type of research is quantitative research that explains or proves the relationship of influence between independent and dependent variables through hypothesis testing. This study used a sample of 100 respondents where the distribution of questionnaires was carried out through online Google forms. Sampling was done using a non-probability sampling method with a purposive sampling technique. The sample consisted of Samsat Drive Thru Batubulan users. The research test tool uses validity test, reliability test, classical assumption, and simple linear regression using the SPSS version. 26. Hypothesis testing in this study using a t-test with the results of the study showing that from the two variables, namely service quality, has a significant positive influence on compliance